Polymorphisms in the canine IL7R 3′UTR are associated with thymic output in Labrador retriever dogs and influence post-transcriptional regulation by microRNA 185. (April 2018) - Holder, Angela; Jones, Gareth; Soutter, Francesca; Palmer, Donald B.; Aspinall, Richard; Catchpole, Brian
Abstract: Interleukin-7 (IL-7) and its receptor (IL-7R) are essential for T cell development in the thymus, and changes in the IL-7/IL-7R pathway have been implicated in age-associated thymic involution which results in a reduction of naïve T cell output. The aim of this study was to investigate the relationship between IL7 and IL7R genetic variation and thymic output in dogs. No single nucleotide polymorphisms (SNPs) were identified in the canine IL7 gene, but a number were present in the canine IL7R gene. Polymorphisms in the IL7R exon 8 and 3′UTR were found to be associated with signal joint T cell receptor excision circle (sj-TREC) values (a biomarker of thymic output) in young and geriatric Labrador retrievers. Additionally, one of the SNPs in the IL7R 3′UTR (SNP 14 c.1371 + 446 A > C) was found to cause a change in the seed-binding site for microRNA 185 which, a luciferase reporter assay demonstrated, caused changes in post-transcriptional regulation, and therefore might be capable of influencing IL-7R expression. The research findings suggest a genetic link between IL7R genotype and thymic output in dogs, which might impact on immune function as these animals age and provide further evidence of the involvement of IL-7/IL-7R pathway in age-associated thymic involution. Highlights: Changes in the IL-7/IL-7R pathway are involved in thymic involution. Polymorphisms in the canine IL7R 3′UTR are associated with sj-TREC values. SNP 14 (c.1371 + 446 A > C) causes a change in the seed-binding site for miRNA 185. Variation of the seed-binding site influences post-transcriptional regulation by miRNA 185.